Ultrastruktur Morfologi Polen Arundina graminifolia (D.Don) Hochr. (Orchidaceae) - Dina Marvianti; Tesri Maideliza; Syamsuardi Syamsuardi (Universitas Andalas, 2018)
Pollen morphology of three variants of Arundina graminifolia in West Sumatra was examined. The pollen types, shapes, apertures and ornamentations were examined using scanning electron microscope. There was variation of pollen shape between three variant of Arundina graminifolia. There was different of pollen shape white variant to pink and purple variant. The pollen shape of white variant were oblate sferoidal. The prolate shapes were detected at pink and purpe variant. Three variants Arundina graminifolia have the same ornamentation exine that is the reticulum and there kolpus of the same type, namely tri-kolpate and tetra-kolpate